Dual Function Radar and Communication Waveform Design Based on Sub-pulse Hybrid Modulation - Yu LIU; Junhao ZHANG; Xue YAO; Xianxiang YU; Guolong CUI (Leida xuebao)
To address the low data rate issue in the design of Dual-Function Radar-Communication (DFRC) waveforms with radar detection as the primary function, this paper proposes an information modulation method for multiple sub-pulse structure waveforms called Sub-pulse Hybrid Modulation (SHM). The proposed SHM method utilizes time-, spectral-, and polarization-domain features from inter-subpulse and intra-subpulse sources to convey information. The DFRC waveform design problem is formulated based on minimizing cross- and auto-correlation Peak Sidelobe Levels (PSL), while considering constant envelope and SHM constraints. To tackle the resulting nonconvex and nondeterministic polynomial-hard optimization problem, the Spectral Majorization Minimization (SMM) algorithm is employed to monotonically decrease the objective function value. Furthermore, this paper explores an echo processing method that makes the Doppler frequency at the first zero point of the zero-delay intercept of the fuzzy function \begin{document}$ L - 1 $\end{document} times higher than that of the conventional waveform, where L is the number of sub-pulses. This enhancement ensures high Doppler tolerance for the DFRC waveform and enables effective detection of high-speed targets.